The moral importance of reflective empathy - Persson, I; Savulescu, J (Springer Verlag, 2017)
This is a reply to Jesse Prinz and Paul Bloom’s skepticism about the moral importance of empathy. It concedes that empathy is spontaneously biased to individuals who are spatio-temporally close, as well as discriminatory in other ways, and incapable of accommodating large numbers of individuals. But it is argued that we could partly correct these shortcomings of empathy by a guidance of reason because empathy for others consists in imagining what they feel, and, importantly, such acts of imagination can be voluntary – and, thus, under the influence of reflection – as well as automatic. Since empathizing with others motivates concern for their welfare, a reflectively justified empathy will lead to a likewise justified altruistic concern. In addition, we argue that such concern supports another central moral attitude, namely a sense of justice or fairness.